The Hsp70-chaperone machines in bacteria - Mayer, Matthias P. (Frontiers in molecular biosciences, 2021)
The ATP-dependent Hsp70s are evolutionary conserved molecular chaperones that constitute central hubs of the cellular protein quality surveillance network. To no other chaperones a comparable range of functions has been assigned. Through a multitude of functions Hsp70s are involved in many cellular control circuits for maintaining protein homeostasis and have been recognized as key factors for cell survival. Three mechanistic properties of Hsp70s are the basis for their high versatility. First, Hsp70s bind to short degenerate sequence motifs within their client proteins. Second, Hsp70 chaperones switch in a nucleotide-controlled manner between a state of low affinity for client proteins and a state of high affinity for clients. Third, Hsp70s are targeted to their clients by a large number of cochaperones of the J-domain protein (JDP) family and the lifetime of the Hsp70-client complex is regulated by nucleotide exchange factors (NEF). In this review I will discuss advances in the understanding of the molecular mechanism of the Hsp70 chaperone machinery focusing mostly on the bacterial Hsp70 DnaK and will compare the two other prokaryotic Hsp70s HscA and HscC with DnaK.
Gesehen am 09.07.2021